An investigation of virial coefficients of gases - Haworth, WS (1969)
The most widely used experimental method for studying the forces between pairs of molecules is the determination of the second compressibility virial coefficient, B, defined by: z = Pvm/RT = 1 + B/Vm + C/V<subm2 + . . . For non-polar gases at temperatures well removed from the normal boiling point, it is relatively easy to measure values of B with adequate accuracy for assessing the merits of various model intermolecular potential energy functions, However, at temperatures little above the normal boiling point, especially for the more polar gases, adsorption effects can prove troublesome. The density balance method can, in principle, give Values of the second compressibility virial coefficient free from adsorption errors. In practice, there remain other drawbacks to such an approach, particularly the notorious instability of the density balance zero point, and the need for the molecular weight of the gas to be very precisely known, or at least constant within very small limits. The recent extensive development of vacuum micro- and ultramicro-balances suggests that the difficulty of instability should now be superable. A simple theoretical consideration of the treatment of data from such a balance shows that adsorption effects which are not compensated in the balance design may be corrected for, to a first order, and second virial coefficients obtained which are accurate to about +5 cm3 mole-1. Continued in thesis ...